Hostile aliens, Hollywood and today's news : 1950s science fiction films and 9/11 - Matthews, Melvin E. (Algora Pub., 2007)
1950s Cold War-era monsters meet 21st century terrorists: this exploration of sci-fi movies examines the similarities and differences between the political environment and popular culture of two eras. This examination and appreciation of 1950s science fiction films includes behind-the-scenes tales about their production and many quotes from those who produced and starred in the films. The author draws parallels between the Cold War fears of the 1950s and 60s and the constant "terrorism alerts" of the September 11th era, exploring how the politics and the psychological climate of the times influences and is reflected in this vehicle of popular culture. This book is the first of its kind, studying the pop culture genre in the wake of the September 11th tragedy. It shows that, whatever the era and whatever the challenges and crises confronting America, many entertainment themes remain the same, reflecting their respective times and the relevant issues. For instance, Godzilla, the only Fifties-era monster to remain a "movie star" beyond that era, could be fashioned to reflect whatever issues dominate the times, be they nuclear war in the Fifties when Godzilla originated to a Seventies Godzilla film about environmental pollution. Conceivably a Godzilla for the age of terrorism is possible. "Them"! the 1954 atomic mutation classic, is the spiritual ancestor of the 2002 film "Eight Legged Freaks." The alien invaders of the Fifties signified a Russian invasion of America, while other films of the genre, such as "Invaders from Mars," depicted aliens utilizing mind control to manipulate humans to commit acts of sabotage, signifying Communist enslavement. If such a film were made now, such invaders could be seen as terrorist masterminds using human slaves to commit terrorist acts. Finally, several Fifties films depicted the end of the world at a time when Americans expected a nuclear war with Russia. The immediate pre-September 11th era witnessed films presenting galactic threats to mankind's existence ("Independence Day," "Deep Impact," "Armageddon"), while the early 2000s witnessed the popularity of the "Left Behind" Christian films dramatizing the Tribulation period in the Book of Revelation.